Use of Digital Technologies for HR Management in Germany: Survey Evidence - Marina Chugunova; Anastasia Danilov (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
Using a survey with 57 German firms, we evaluate the level of digitalization of the human resource management (HRM) function and document perceived benefits and barriers of technology adoption from organizational and individual users' perspectives. The results give reason for optimism. Most of the companies report that the core HR processes are digitized. We do not observe adverse effects of the digital HRM tools on users' job satisfaction and work stress. Still, more than half of companies do not yet use digital tools for strategic HRM decisions. Respondents appreciate the increased speed and cost-efficiency of digital HR processes and associate them with a competitive advantage in talent acquisition. The most prominent barriers to adoption are lack of qualified professionals, high costs, and uncertainty regarding the legal framework. Additionally, we test whether small and medium-sized enterprises differ systematically from larger organizations in how they use digital HRM tools.
Keywords: M12; M15; M50; O33; O52; 330; digital HRM tools; human resource management; digitalization; Germany